Comparison of Activity Levels Measured by a Wrist Worn Accelerometer and Direct Observation in Young Children - K Djafarian; M Hession; JR Speakman; DM Jackson (Tehran University of Medical Sciences, 2005)
Introduction: Physical activity may play a central role in the obesity epidemic. However, most epidemiological research is based on subjective measures of physical activity. The purpose of this study was to validate a wrist worn accelerometer to quantify physical activity of children, by comparison to direct observation. Methods: Data were analysed from 42 children, aged between 3-5 years (22 boys) observed each minute for 2 hours using the Children's Activity Rating Scale (CARS) while wearing the Actiwatch accelerometer. Results: There were significant positive correlation between the mean CARS levels and the mean Actiwatch counts over simultaneous 1-10 minute periods ranging from r= 0.412 to r= 0.631(P< 0.001). Using a cross validation method the data were split in half at random and a predictive equation associating actiwatch scores and CARS scores generated. CARS prediction scores were then compared against actual CARS data in the other half of the sample. There was no significant difference between the predicted and the observed CARS. CARS score could be calculated with a 95% confidence level of plus or minus 0.74 CARS units. Discussion: These data suggest that wrist worn accelerometers are a valid tool for objectively assessing levels of physical activity in young children.